Imperatorin protects H9c2 cardiomyoblasts cells from hypoxia/reoxygenation-induced injury through activation of ERK signaling pathway - Bihong Liao; Ruimian Chen; Feng Lin; Aihuan Mai; Jie Chen; Huimin Li; Shaohong Dong; Zhenglei Xu (Elsevier, 2017)
Background: Imperatorin is a compound found in plants and has been widely used in Chinese medicine for many years. It has many pharmacological effects, including the recently reported anti-apoptotic function, however, the mechanism largely remains unclear. This study is aimed to elucidate the mechanism of Imperatorin's anti-apoptotic function. Methods: A model of hypoxia and reoxygenation (H/R) treated h9c2 cardiomyoblasts was successfully constructed. The cells were treated with H/R condition, and followed by adding Imperatorin alone, Imperatorin with ERK inhibitor and/or ERK inhibitor alone, to examine the cell viability by Cell Counting Kit-8 assay, cell apoptosis rate by flow cytometry, and ERK expression by Western-blot under different conditions. Results: The results showed that imperatorin exerted protective effect on h9c2 cells from H/R injure. It was also found that it not only increased cell viability but also reduced the apoptotic rate for H/R treated h9c2 cells. The experiments also demonstrated that imperatorin could upregulate the expression levels of both ERK1 and ERK2, which is a key step in ERK signaling pathway activation. Conclusions: These findings provided evidence that imperatorin could increase the cell viability and lower apoptotic rate in H/R treated h9c2 cells, and could also enhance the expression of ERK1/ERK2, demonstrating imperatorin's protective effect on H/R injured h9c2 cells through ERK signaling pathway. Keywords: Imperatorin, Hypoxia/reoxygenation, H9c2 cardiomyoblasts, ERK signaling pathway, Apoptosis